Tattoo taboos in the workplace - Low, Justin Lingyi (2015)
Although tattoos is becoming gradually accepted in the Singapore society, tattoos are still being considered deviance in certain areas of the society. One such places whereby tattoos remain a taboo and still frown upon will the workplace. This research paper studies the link between discrimination and tattooed employees in Singapore. It examines the meanings of tattoos for different people and how these meanings affect the tattooed employees in their workplace. It will also reveal what hiring managers think of tattooed individuals, whether tattooed employees face an unfair disadvantage in the workforce and what are the differences between someone who has a visible tattoo and someone who has a tattoo which can be concealed.